A New Type of Transverse Flux Permanent Magnet Rim Motor and Its Modeling Analysis. Issue 1 (1st May 2022) - Lin, Bo; Gao, Jin; Liu, Yonghui; Zhan, Pengfei
Abstract: In this paper, a new type of transverse flux permanent magnet rim motor is obtained by combining transverse flux permanent magnet motor with shaftless rim motor. When a sinusoidal current is passed through the stator of the motor, a rotating magnetic field will be generated. The rotating magnetic field interacts with the constant magnetic field generated by the rotor magnet, and the interaction will drive the motor to rotate. The new motor has the advantages of high power, low noise, small vibration and small volume, and is suitable for marine propulsion and other fields. This paper introduces the special magnetic field distribution of the new motor, and uses the 3D finite element analysis method to analyze the electromagnetic field of the motor's no-load and load conditions. The paper will verify the correctness and superiority of the model.